Biomass and Habitat Use of Guinea Fowl (Numidia meleagris) in Dinder Biosphere Reserve, Sudan, during the Dry Season* - Ibrahim, Mubarak Ali; Hashim, Ibrahim M. (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was conducted in the Dinder Biosphere Reserve during the dry seasons of 2007 and 2008. The objective of the study was to determine biomass and habitat use of Guinea fowl (Numidia meleagris) in the various ecosystems of the reserve. Loop and nearest neighbour methods were used for measuring the vegetation attributes. The density of Guinea fowl was calculated in strip transects that were 500 m long and 200 m wide by the double sampling procedure. First, the number of Guinea fowl was estimated and then counted directly. Second, a predictive model was developed from the relationship between the counted and the estimated variables. Subsequently, the number of the birds was only estimated and the actual count was predicted from the model. Guinea fowl was captured by mist nets and locally made traps, weighed and morphometric measurements were taken. Biomass was calculated as the product of density and the live weight. The density of Guinea fowl was high around the mayas (meadows) and riverine ecosystems. The total biomass in the reserve was 93.76 kg/km². The vegetation attributes around the mayas varied considerably. The percentage of litter was high in some mayas and low in others; bare land was relatively high in most of the reserve area but burnt areas were very low. Trees of high densities included Acacia seyal, Combretum sp., Balanites aegyptiaca, Ziziphus-spina-christi and Acacia polycantha. Of these, Guinea fowl roosted only on A. seyal and Combretum sp.